EFEKTIVITAS BERMAIN KULIT JERUK BALI TERHADAP PERKEMBANGAN KREATIVITAS ANAK DI TAMAN KANAK-KANAK KASIH IBU PASAMAN TIMUR - Sepgita Asri; Rivda Yetti; Asdi Wirman (Universitas Bengkulu, 2019)
This study aims to find out how effective playing of grapefruit skin to the development of children's creativity in the kindergarten Kasih Ibu of East Pasaman. The research using Quantitative approach in the form Quasi Experiments. Technique of collecting data using test, in the form of statement as 4 point statement and technique of data analysis using normality test, homogeneity test, hypothesis test, data collecting tool used statement sheet. Then the data is processed by difference test (t-test). Based on data analysis, the mean of experimental group test result is 88,12 and SD is 9,25 while in control group is 81,87 and SD equal to 8,38. In hypothesis testing obtained tcount of 2.561 and table of 2.07387 at the level of real ? = 0,05 and dk = 18. Then it can be concluded that foam art painting is effective in developing fine motor in child kindergarten in Kasih Ibu of East Pasaman.